Effects of some of the regional Turkish fermented foods and medications on respiratory alcohol levels - (:unkn) unknown (My University, 2014)
0

Background/aim: Alcohols are used in many areas like medicine and industry. They may be naturally found in some fruits and vegetables secondary to fermentation. According to the traffic law in Turkey, professional drivers are prohibited from driving while they are under the influence of alcohol; nonprofessional drivers are allowed to drive vehicles with a blood alcohol level of up to 50 mg/dL. The aim of this research is to determine whether or not consumed medicine or fermented, nonalcoholic beverages cause false positive results in breathalyzer tests. Materials and methods: In this research, we used nonalcoholic fermented foods and 6 medicines. After the use of these materials, we measured breath alcohol level at 1, 3, 5, 15, and 30 min with a breathalyzer. Results: False positive results were obtained only with Dişinol and cologne. Other drugs and nutrients did not cause any false positivity in breathalyzer tests. Conclusion: At the end of the research, we observed that some substances caused false positive results, even if people did not use any alcohol. If there is any suspicion of the measured values, then measurements should be repeated. If a person cannot be sure of the reliability of the breathalyzer measurements, the person should consult other centers without losing time.
Keywords: Cerrahi